Dampak Strategi Kooperatif Tipe Numbered Head Together (NHT) Pada Pembelajaran Pendidikan Agama Kristen di SD Kaliban Batam - Alpionika, Widie; Tanama, Yulia Jayanti (Sekolah Tinggi Teologi Kharisma, 2023)
Kaliban Elementary School students are passive in the learning process, resulting in students becoming bored, failing to focus, and decreasing grades. As a teacher of Christian Religious Education must have a high initiative to attract the attention of students, so that the learning process takes place active students. This research method aims to determine the impact of implementing NHT type cooperative learning strategies on Christian Religious Education. The study used qualitative methods by conducting interviews and observations. The results obtained from this study are: first, the learning outcomes of students who have high abilities are as good as students with medium and low abilities, second, students are more active in collaborating or working well together to find answers, third, students individually responsible as a member of the group, and fourth, increase students' understanding of the material being studied Peserta didik SD Kaliban pasif dalam proses pembelajaran, mengakibatkan peserta didik menjadi bosan, gagal fokus, dan nilai mengalami penurunan. sebagai seorang guru Pendidikan Agama Kristen harus memiliki inisiatif yang tinggi untuk menarik perhatian peserta didik, supaya pada proses pembelajaran berlangsung peserta didik aktif. metode penelitian ini bertujuan untuk mengetahui dampak implementasi strategi pembelajaran kooperatif tipe NHT pada Pendidikan Agama Kristen. Penelitian menggunakan metode kualitatif dengan melakukan wawancara dan observasi. Hasil yang diperoleh dari penelitian ini yaitu: (1) hasil belajar peserta didik yang memiliki kemampuan tinggi sama baiknya dengan siswa memiliki kemampuan sedang dan rendah, (2) peserta didik lebih aktif berkolaborasi atau bekerjasama dengan baik untuk menemukan jawaban, (3) peserta didik bertanggungjawab secara individu sebagai anggota kelompok, dan (4) meningkatkan pemahaman peserta didik terhadap materi yang dipelajari.